Simultaneous determination of aromatic amino acids in human blood plasma by capillary electrophoresis with UV‐absorption detection. Issue 10 (10th April 2015) - Forteschi, Mauro; Sotgia, Salvatore; Assaretti, Stefano; Arru, Dionigia; Cambedda, Debora; Sotgiu, Elisabetta; Zinellu, Angelo; Carru, Ciriaco
Abstract : Phenylalanine, tyrosine, and tryptophan, also known as aromatic amino acids, are involved in many physiological and pathophysiological conditions and are indicative of the liver and kidney function. In this work, we describe a simple and accurate method for their simultaneous quantification, in a single capillary electrophoresis run. This method requires minimal sample manipulation, no derivatization procedures, and methyl tryptophan as internal standard. The human blood plasma sample was precipitated using sulfosalicylic acid and the supernatant was used for the analysis. All the analytes were baseline resolved within 16 min and detected at 200 nm using Tris phosphate 80 mmol/L at pH 1.4 as the background electrolyte. The proposed method showed good linearity ( r = 0.998) and repeatability (intra‐assay RSD < 2.78%, interassay RSD < 5.4%) for all the analytes. The limit of quantification was 13 μmol/L for phenylalanine and 5 μmol/L for tyrosine and tryptophan. The method suitability was tested measuring aromatic amino acids level in 20 chronic kidney disease patients at basal level and after simvastatin/ezetimibe treatment.